Jere R. Behrman. Macroeconomic policy in a developing country : the Chilean experience. [Amsterdam] : North-Holland Publishing Company, 1977 - Carrillo Arronte, Ricardo (El Colegio de México A.C., 1978)
JERE R. BEHRMAN, Macroeconomic Policy in a Developing Country: The Chilean Experience. North-Holland Publishing Company, 1977.